2011
DOI: 10.5713/ajas.2011.11076
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Nutrient Characteristics, Ruminal Solubility and Degradability of Spent Mushroom (Agaricus bisporus) Substrates for Ruminants

Abstract: This study was conducted to evaluate the yield, nutrient characteristics, ruminal solubility, degradability and disappearance of spent mushroom (Agaricus bisporus) substrates for ruminants. The annual yield of spent Agaricus bisporus substrates was measured to be about 210,000 tons (M/T) in South Korea. The surface soil-removed spent substrates had nutritional characteristics of high crude ash (375 g/kg) and Ca (32 g/kg), medium protein (134 g/kg CP), and high fiber (384 g/kg NDF on a DM basis). Compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…Interestingly, SMS can be used as animal feed, as shown in feed research involving livestock [17,18] and poultry [19]. Xu et al [20] showed that an SMS level of 6.5% in the dry matter of cattle's diet can be recommended for silage based on the total mixed ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, SMS can be used as animal feed, as shown in feed research involving livestock [17,18] and poultry [19]. Xu et al [20] showed that an SMS level of 6.5% in the dry matter of cattle's diet can be recommended for silage based on the total mixed ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al . (), who recently studied spent Agaricus bisporus substrates, reported that the increased protein and decreased fiber contents in the substrates was the impact of mycellia activity during the A. bisporus mushroom cultivation, suggesting that SMS could be used as a potential roughage source for ruminants. SMS can be easily digested by ruminants due to the enzymatic conversion processes that occur during mushroom cultivation (Streeter et al .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a significant increase in total phosphorus was observed in the one-year interval cultivation regime, indicating that the amount of phosphorus increase was greater than the amount of phosphorus lost in the one-year interval cultivation regime. We hypothesize that spent mushroom compost left after the harvesting of fruiting bodies would add a certain amount of macronutrients like nitrogen, phosphorous and potassium (NPK) ( Kim et al, 2011 ). However, this hypothesis needs to be further tested in the future.…”
Section: Discussionmentioning
confidence: 99%